Keterkaitan Nilai-Nilai Akuntansi Syariah dalam Tradisi Pernikahan Lahat: Sebuah Epistemologi Islam - Eogenie Lakilaki (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2026)
This study explores the embodiment of sharia accounting values in traditional wedding practices in Lahat Regency, South Sumatra, through an Islamic epistemological lens. Using a qualitative interpretive approach, it examines indigenous rituals as culturally embedded accounting practices that govern financial and social obligations. The findings indicate that these traditions reflect the core objectives of Maqasid al-Shariah: hifz al-diin (preservation of religion) through the sanctification of marriage, hifz al-nafs (life) via collective responsibility and social harmony, hifz al-‘aql (intellect) through ethical deliberation and knowledge transmission, hifz al-nasl (lineage) by regulating marital legitimacy, and hifz al-maal (wealth) through transparent and fair financial arrangements. These practices function as a decentralized, community based form of Islamic accounting governed by ‘urf (custom) in alignment with sharia principles. This study challenges institution centric perspectives in Islamic accounting and contributes to a culturally grounded framework for Islamic financial ethics rooted in lived community practices.